PENERAPAN SMART GOVERNANCE DALAM PENGGUNAAN APLIKASI M-PASPOR DI KOTA PALEMBANG - Juliastika, Arifah; Kencana, Novia; Isabella, Isabella (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
The purpose of this research is to find out the implementation of Smart Governance in the use of the M-Passport application in the work area of the Immigration Office Class I Palembang City. The research method used is a qualitative method using a case study approach using various data collection procedures carried out in depth on an object, individual, group, etc. The results of this research and discussion use the theory of Gartner which has four indicators, namely Web presence (web presence). The results of this research and discussion use the theory of Gartner which has four indicators, namely Web presence (web presence) from the ease of accessing the M-Passport application can be said to be quite good, this is because there are still many negative responses from the public regarding the M-Passport application system, Interaction (interaction) at this stage is good because there are features that support getting information and there is also ease of sending and downloading application files, Transaction at this stage has gone very well, Transformation at this stage can be said to be good because there are many service innovations made by the Immigration Office Class 1 Palembang City as a tangible manifestation of commitment in making it easier for the communityBased on the results of research and discussion in this study, it can be concluded that it is good and is at the Transaction stage because the application can be used to transact both for the community and service providers. Keywords: E-Government; Smart Governance; M-Passport; Passport